3D thermodynamics and parameters analysis of the external combustion hot blast stove - YuFeng Gan; Chichun Lee; Tiaoyuan Wu; Junjie Chen; Xiangdong Gao (Advances in Mechanical Engineering)
The external combustion hot blast stove is widely used in the steelmaking industry due to the advantage of providing a large amount of high-temperature and stable hot blast for blast furnaces. To research the thermal efficiency and stability of external combustion hot blast stoves, the non-equilibrium porous medium model coupled with transient thermal analysis is used to discuss the characteristics of two types of external combustion hot blast stoves during the cyclic operation process. In this paper, a comparison of the numerical data and in situ data during one cycle to ensure the accuracy of the calculation, which of the results showed that the temperature maximum relative error value is within 3%. The numerical results displayed that the velocity and temperature distribution of fluid are mainly affected by pressure, flow rate, cycle time, and geometric structure, where the hot blast temperature is affected by the cycle time but the distribution of velocity and relative pressure are affected by the height of hot blast branch. It can be concluded that the flow field and the structure of type A hot blast stove are more stable than that of type B by comparing the results of two types of hot blast stoves.